2018
DOI: 10.1093/jxb/ery350
|View full text |Cite
|
Sign up to set email alerts
|

FLOWERING LOCUS T2 regulates spike development and fertility in temperate cereals

Abstract: FLOWERING LOCUS T2 (FT2) is expressed in the distal part of the developing wheat spike and contributes to the regulation of the number of spikelets per spike.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
93
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 86 publications
(106 citation statements)
references
References 37 publications
10
93
3
Order By: Relevance
“…Since there is a known positive feedback regulatory loop between VRN1 and FT1 (Shaw et al, 2019), we compared the FT1 transcript levels in the leaves of the different VRN1 , FUL2 and FUL3 mutant combinations. FT1 transcript levels higher than ACTIN were observed in leaves of 4-week old plants carrying the VRN1 wild type allele, but were detected only after 10 weeks in plants carrying the vrn1 -null allele (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Since there is a known positive feedback regulatory loop between VRN1 and FT1 (Shaw et al, 2019), we compared the FT1 transcript levels in the leaves of the different VRN1 , FUL2 and FUL3 mutant combinations. FT1 transcript levels higher than ACTIN were observed in leaves of 4-week old plants carrying the VRN1 wild type allele, but were detected only after 10 weeks in plants carrying the vrn1 -null allele (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Low expression levels of VRN-H1, BM3 and BM8in Ubi::HvFT4 plants might have caused the 379 delay in spikelet initiation However, and reduced floret fertility and grain set. It has already 380 been demonstrated that FT1, FT2, and the BM genes affect floret fertility and grain set (Digel 381 et al, 2015;Ejaz et al, 2017;Shaw et al, 2019). We therefore conclude that the downregulation 382 of BM-like genes and consequently HvFT1 and HvFT2 in the inflorescence has contributed to 383 the reduction in fertility and grain set of the main and axillary shoots.…”
Section: Discussion 340mentioning
confidence: 64%
“…While HvFT1 is only 86 expressed and induces flowering under LD conditions, the homolog HvFT3 is expressed and 87 promotes reproductive development under long and short-day conditions (Mulki et al, 2018). 88 Experiments in wheat, barley, Brachypodium and rice suggested that FT2 is a floral promoter, 89 downstream of FT1 and expressed in the leaf as well as in the inflorescence (Kikuchi et al, 90 2009;Lv et al, 2014;Digel et al, 2015;Shaw et al, 2019). 91…”
Section: Introduction 37mentioning
confidence: 99%
See 1 more Smart Citation
“…Cadenza. Expression of the gene is higher in Avalon and higher expression of FT2 has been 4 3 1 shown to cause earlier flowering in (Shaw et al, 2019). Eight informative recombinants were grown together with 3A NIL controls and the parents were repeated with Cadenza alleles at the 3A locus resulting in a crop which was later 4 4 2 heading (by one day) and taller (11.7cm).…”
mentioning
confidence: 99%